2018
DOI: 10.1016/j.neuropsychologia.2018.03.020
|View full text |Cite
|
Sign up to set email alerts
|

The role of the temporoparietal junction in implicit and explicit sense of agency

Abstract: The experience of being in control of one's actions and thier outcomes is called the sense of agency. This is a fundamental feature of our human experience, and may underpin important social functions such as morality and responsibility. Sense of agency can be measured explicitly, by asking people to report their experience, or implicitly by recording the perceived time interval between actions and outcomes (intentional binding). The current studies used transcranial direct current stimulation to assess the ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 34 publications
(49 reference statements)
0
9
0
Order By: Relevance
“…Importantly, because of the assumed causal link between the two, we expect an anti-correlation within the same individuals (Corlett et al, 2019); e.g., participants with less sensory attenuation and stronger re-afferent signals should also report more conditioned hallucinations. Stronger evidence in favor of our theory could be obtained from causal, virtual lesion studies such as TMS studies: stimulation of regions critically involved in ego-centric inferences such as cerebellum (Blakemore et al, 1998;Synofzik et al, 2008c) or the temporo-parietal junction (TPJ) (Hughes, 2018) should engender hallucinations in participants (Arzy et al, 2006).…”
Section: Explanatory Power and Novel Predictionsmentioning
confidence: 94%
“…Importantly, because of the assumed causal link between the two, we expect an anti-correlation within the same individuals (Corlett et al, 2019); e.g., participants with less sensory attenuation and stronger re-afferent signals should also report more conditioned hallucinations. Stronger evidence in favor of our theory could be obtained from causal, virtual lesion studies such as TMS studies: stimulation of regions critically involved in ego-centric inferences such as cerebellum (Blakemore et al, 1998;Synofzik et al, 2008c) or the temporo-parietal junction (TPJ) (Hughes, 2018) should engender hallucinations in participants (Arzy et al, 2006).…”
Section: Explanatory Power and Novel Predictionsmentioning
confidence: 94%
“…Intentional binding can be modulated by the frontal regions, especially the pre-supplementary motor area (pre-SMA) (Moore, Ruge, Wenke, Rothwell, & Haggard, 2010) and the left dorso-lateral prefrontal cortex (Khalighinejad, Di Costa, & Haggard, 2016). In contrast, explicit sense of agency can be modulated by parietal regions, such as the right angular gyrus (Farrer, Frey, et al, 2008;Farrer & Frith, 2002) and the right temporoparietal junction (Hughes, 2018). However, meta-analytic study suggests that not only temporoparietal junction but also pre-SMA is associated with explicit sense of agency (Sperduti, Delaveau, Fossati, & Nadel, 2011).…”
Section: Relationship Between Agency Judgment and Intentional Bindingmentioning
confidence: 99%
“…Given this, it is plausible that degree of intentional binding is (in)directly associated with the degree of perceived sense of agency. Indeed, brain imaging and stimulation studies have suggested that, although frontal and parietal cortices are associated with agency judgment (Farrer, Frey, et al, 2008;Farrer & Frith, 2002;Hughes, 2018) and intentional binding (Khalighinejad et al, 2016;Moore et al, 2010), respectively, these two aspects of agency may recruit a shared neural mechanism. Explicit sense of agency can also relate to frontal region activities (Nachev et al, 2005;Nachev et al, 2007;Sperduti et al, 2011) and crucially, to front-parietal functional connectivity (Chambon et al, 2013).…”
Section: Intra-and Inter-individual Correlation Between Explicit and mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, temporal mismatches between action and sensory outcome are associated to activation in posterior parietal regions, such as the superior parietal lobule (Leube, Knoblich, Erb, & Kircher, ), the precuneus (Farrer et al, ; Farrer & Frith, ), and the temporo‐parietal junction (Leube, Knoblich, Erb, Grodd, et al, ; Leube, Knoblich, Erb, Schlotterbeck, & Kircher, ; Limanowski, Kirilina, & Blankenburg, ; van Kemenade et al, ). Finally, activation in the temporo‐parietal junction, and especially in the angular gyrus, is associated with explicit awareness of non‐agency, that is, the subjective experience of not having caused a sensory event (Farrer et al, ; Hughes, ).…”
Section: Introductionmentioning
confidence: 99%